PARTICIPATORY MONITORING: LEARNED LESSONS IN THE MANGROVE CRAB UCIDES OCCIDENTALIS (ORTMANN, 1897) FISHERY IN ECUADOR - Zambrano, René (2022)
The mangrove crab fishery has had participatory monitoring since 2011. The objective of this work was to show the lessons learned in the implementation and development of participatory monitoring of the mangrove crab Ucides occidentalis (Ortmann, 1897) in Ecuador. The work was carried out as a descriptive case study. The level of compliance of the fishing organizations involved was estimated considering the information reported by the Public Institute of Aquaculture and Fisheries Research. The level of compliance decreased over time despite the fact that the number of organizations increased between 2011 and 2013. In 2013, the overall compliance was less than 40% with a negative trend, since December 2011. Among the best organizations, the Compliance level reached 60% in 2013, with a negative trend since January of the same year. The lessons learned showed that the follow-up presented a level of compliance with a negative trend over time; furthermore, the increase in the number of participating organizations did not ensure an increase in the compliance of fishing organizations. Participatory monitoring may fail in the generation of scientific information on the fishery resource. Apparently, participatory monitoring continues to work. Some fishing organizations (e.g., Mondragón) collect and submit data, but the level of compliance and the number of participating organizations are unknown.